PENERAPAN MODEL EXPLICIT INSTRUCTION (EI) UNTUK MENINGKATKAN ANTUSIASME DAN PRESTASI BELAJAR - Ristika Pratiwi (UNIB Press, 2023)
This study purpose to describe the application of learning methods to improve students' enthusiasm and learning achievement. The research method used is Classroom Action Research and uses Quasi Experiments. The subjects of this study were students of class X SMA Negeri 3 in Rejang Lebong in the first semester 2 of the 2021/2022 academic year. The number of students for the CAR class, namely class X IPS 1, amounted to 35 people, for the control class, namely X IPS 2, which amounted to 35 people. The method used in data collection in this study used learning observation sheets, enthusiasm observation sheets and student learning outcomes tests. Data analysis used the analysis of the average data score and the t-test which consisted of a difference test between cycles and a different test of two unrelated samples. The results showed that the application of thelearning Explicit Instruction (EI) model could increase students' enthusiasm, learning achievement and the effectiveness of the application of the learning Explicit Instruction (EI) model in Civics subjects for class X IPS SMA Negeri 3 in Rejang Lebong